2021
DOI: 10.3390/horticulturae7080250
|View full text |Cite
|
Sign up to set email alerts
|

Growth Response of Ginger (Zingiber officinale), Its Physiological Properties and Soil Enzyme Activities after Biochar Application under Greenhouse Conditions

Abstract: This study aimed to investigate the effects of biochar (1%, 2%, and 3%) on seed germination, plant growth, root morphological characteristics, and physiological properties of ginger (Zingiber officinale) and soil enzymatic activities. Pot experiments under greenhouse conditions at 24 °C (day) and 16 °C (night) showed after six weeks that biochar additions of 2% and 3% significantly increased seed germination, plant height, leaf length, leaf number, as well as shoot and root dry weights compared to the control.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 50 publications
(76 reference statements)
1
18
0
Order By: Relevance
“…Zhang et al [25] reported that the composition of biochar includes carbon, nitrogen, hydrogen, and lower nutrient elements, such as K, Ca, Na, and Mg. It plays an important role in soil nutrient availability, adsorption, and soil enzyme activity [26][27][28][29]. He et al [30] indicated that biochar enhanced the absorption of nitrogen (N), phosphorus (P), and potassium (K) by tomato.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [25] reported that the composition of biochar includes carbon, nitrogen, hydrogen, and lower nutrient elements, such as K, Ca, Na, and Mg. It plays an important role in soil nutrient availability, adsorption, and soil enzyme activity [26][27][28][29]. He et al [30] indicated that biochar enhanced the absorption of nitrogen (N), phosphorus (P), and potassium (K) by tomato.…”
Section: Introductionmentioning
confidence: 99%
“…This improvement is due to the role of arbuscular mycorrhizal fungi in increasing absorption of water and nutrients, and enhances transport of immobile mineral elements through exploring larger volumes of the soil by mycorrhizal hyphae to stimulate the growth of plants [46]. These results are in harmony with studies by Davies et al [17] on pepper, Ruiz-Lozano and Azcon [18] on lettuce, Auge et al [19] on the common bean, Ruiz-Lozano et al [20] on soybean, Ortas [21] on maize, wheat and cotton, Roldan et al [23] on juniperus, Ortas and Rattan [24] on pepper, wheat and maize, Tobar et al [25] on lettuce, Igiehon et al [26] on soybean, Jabborova et al [27] on spinach, Jabborova et al [28] on ginger, Zewail et al [29] on stevia and Ortas [47] on twelve plant species.…”
Section: Effect Of Arbuscular Mycorrhizal Fungimentioning
confidence: 87%
“…In addition, mycorrhizal fungi increase the resistance to drought and salinity stresses as well as pests and soil-borne diseases and improve growth and osmotic adjustment through stimulating the production of growth-regulating substances [16]. In this field, many studies such as those by Davies et al [17] on pepper, Ruiz-Lozano and Azcon [18] on lettuce, Auge et al [19] on the common bean, Ruiz-Lozano et al [20] on soybean, Ortas [21] on maize, wheat and cotton, Karandashov and Bucher [22], Roldan et al [23] on Juniperus, Ortas and Rattan [24] on pepper, wheat and maize, Tobar et al [25] on lettuce, Igiehon et al [26] on soybean, Jabborova et al [27] on spinach, Jabborova et al [28] on ginger and Zewail et al [29] on stevia were conducted.…”
Section: Introductionmentioning
confidence: 99%
“…India is the top country for spices supply in the global market, followed by several other countries, including Indonesia, Malaysia, Pakistan, Australia, Spain, Egypt, and Tanzania. Herbal plants are a major source of traditional medicine and modern medicine and play a major role in the world [3][4][5][6][7]. Ginger is one of the most popular, high valued spices and is well known in human communities of the world [8].…”
Section: Introductionmentioning
confidence: 99%